1995
DOI: 10.1029/94jd02828
|View full text |Cite
|
Sign up to set email alerts
|

Biogenic sulfur emissions and aerosols over the tropical South Atlantic: 3. Atmospheric dimethylsulfide, aerosols and cloud condensation nuclei

Abstract: We measured dimethylsulfide in air (DMSa) and the number concentration, size distribution, and chemical composition of atmospheric aerosols, including the concentration of cloud condensation nuclei (CCN), during February‐March 1991 over the tropical South Atlantic along 19°S (F/S Meteor, cruise 15/3). Aerosol number/size distributions were determined with a laser‐optical particle counter, condensation nuclei (CN) concentrations with a TSI 3020, and cloud condensation nuclei (CCN) with a Hudson‐type supersatura… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

24
86
1

Year Published

1996
1996
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 155 publications
(111 citation statements)
references
References 70 publications
24
86
1
Order By: Relevance
“…Over the blue ocean, a wide tail of large drops occurs already at cloud base (Fig. 4A), apparently because of the large sea salt aerosols (16) that are present in the trade wind BL in sufficient quantities to induce such an effect (17). The surface wind during that flight was ϳ8 m s Ϫ1 , just enough to produce white caps and sea spray.…”
Section: R E S E a R C H A R T I C L Ementioning
confidence: 96%
“…Over the blue ocean, a wide tail of large drops occurs already at cloud base (Fig. 4A), apparently because of the large sea salt aerosols (16) that are present in the trade wind BL in sufficient quantities to induce such an effect (17). The surface wind during that flight was ϳ8 m s Ϫ1 , just enough to produce white caps and sea spray.…”
Section: R E S E a R C H A R T I C L Ementioning
confidence: 96%
“…2 The photooxidation of DMS is the dominant sulfate source in the remote marine environment. 3,4 However, the number of CCN associated with DMS emissions remains uncertain. Homogeneous nucleation of sulfuric acid vapor generated from DMS has been proposed as a source of new particles, as happens in other parts of the atmosphere.…”
Section: Discussionmentioning
confidence: 99%
“…5 This mechanism tends to be highly localized in its effects, 6,7 whereas measurements at remote marine sites suggest a more ubiquitous and steady background population of sulfuric acid-based aerosols with concentrations in the range of 100-1000/cm 3 . 3,4,8,9 It is also known that homogeneous nucleation of sulfuric acid is not generally favored in the MBL-except in isolated locales-because of pre-existing particles, which scavenge free acid vapor and prevent the build-up of concentrations sufficient for nucleation under reasonable conditions. 10 Another source of boundary layer aerosols is associated with entrainment from the free troposphere.…”
Section: Discussionmentioning
confidence: 99%
“…[17][18][19][20][21][22][23] These findings, however, lacked the spatial and temporal coverage necessary to resolve whether this DMS-CCN coupling is widespread and, therefore, relevant for global climate processes. Other works suggested that globally, and especially in the northern hemisphere, most of the atmospheric aerosols and CCN do not come from DMS oxidation but from continental sources.…”
Section: What Is the Climatic Factor That Drives Oceanic Dms Productimentioning
confidence: 99%